Upaya Pengurus Dalam Memakmurkan Masjid Raya Nagari Ujung Gading Kecamatan Lembah Melintang Kabupaten Pasaman Barat - Dewi Febriani; Sarwan Sarwan; Fitri Ayu Lestari (Universitas Islam Negeri Imam Bonjol Padang, 2020)
Masjid Raya Nagari Ujung Gading has earned the title as the oldest, largest, grandest mosque and has become a model, but the quality and quantity of congregation do not match the title it carries. In this regard, this study aims to describe the efforts made by the management in prospering Masjid Raya Nagari Ujung Gading. This research is a field research (Field Research), using a qualitative descriptive method, namely a method that describes and describes events in accordance with actual conditions. . The results showed that the efforts made by the management to improve the quality and quantity of congregation at the Nagari Ujung Gading Raya Mosque in the fields of worship, preaching as well as supporting factors and inhibiting factors.